Advantages of using composite alloys for internal combustion engine pistons - Mirosław Kowalski (Archives of Transport, 2020)
Combustion engine pistons are subject to variable mechanical and thermal loads, and to variable deformations. The article presents the possibilities of using novel composite alloys for the construction of pistons for combustion engines. The novel alloys make it possible to meet high demands, especially for highly load designs, which practically cannot be met by conventional alloys used so far. These high requirements relate to the weight of the pistons, high temperature strength, alloy crystalline structure, abrasive wear resistance, dimensional stability. The requirements for pistons have an impact on the durability of the engine's operation, the level of noise emissions; exhaust gas blow-by into the crankcase, the level of emitted toxic exhaust components, mainly hydrocarbons. The research covered metallography (chemical composition, microstructure), material strength, abrasive wear, and thermal expansion. Investigations of the alloy crystallization process during casting were carried out using the Differential Thermal Analysis (DTA) method. The castings were used for metallographic tests. The strength of the samples was tested at room temperature (20° C) and elevated temperature (up to 350° C) on a testing machine equipped with a special climatic chamber. In particular, the article presents Thermal Derivative Analysis curves and representative microstructures of conventional AlSi12 alloy and the novel composite alloy; dependence of the tensile strength versus temperature for the samples of the novel alloy with various nickel content 2% and 4 %; comparison of the tensile strength for conventional alloy and the novel alloy at ambient and 250° C temperature; comparison of abrasive wear of samples, made of novel aluminium alloy and different cast iron; course of the linear expansion coefficient versus temperature for the conventional AlSi12 alloy with incorrect heat treatment; course of the linear expansion coefficient versus temperature for one of tested silumin alloy which expansion coefficient during sample cooling is smaller than during sample heating; course of the linear expansion coefficient versus temperature for the novel composite silumin alloy, after correct heat treatment. The great benefits of using this novel alloy and the introduction of novel alloying elements (in-Situ) have been confirmed in engine research.